الجدل المقاصدي في الاجتهاد الفقهي المعاصر - نوال قاوز (Universty of El-oued جامعة الوادي, 2024)
الملخص: في سبيل التأصيل والتفعيل للبواعث المعتبرة على التشريع في الاجتهاد الفقهي المعاصر مناشدة للصواب، وقع جدل كبير بين المجتهدين المعاصرين، يرجع بالأساس إلى تباين منطلقاتهم العقدية ومرجعياتهم المذهبية، وإلى تباين المعارف العلمية الدقيقة ومدى تكاملها بينهم، إضافة إلى تباينهم في الملكات التنزيلية أيضا. وقد خلص البحث من خلال معالجة جملة من المسائل الفقهية المعاصرة إلى أنه لابد من ضوابط من شأنها تحقيق أكبر قدر من التوافق بين المقاصدين المعاصرين أهمها: الإخلاص والالتجاء إلى الله -عز وجل- وسؤاله الإعانة والتوفيق ابتداءً، ثم أهلية المتصدي للعملية الاجتهادية؛ بأن يكون متضلّعا بالشريعة وعلومها، له نظرة نقدية شجاعة، يروم الاستفادة من جميع المذاهب الفقهية الإسلامية المختلفة، ويراعي الواقع ويسبر أغواره ضمن عمل مؤسساتي متخصص تتلاقح فيه المعارف والخبرات. Résumé : انجلزية In the pursuit of elucidating and activating the influential factors in contemporary jurisprudential ijtihad, a significant debate has arisen among modern jurists. This debate is primarily attributable to the divergence of their religious foundations and jurisprudential references, as well as variations in their precise scholarly knowledge and the degree of integration among them. Additionally, their interpretations of divine texts differ. The research has concluded that there is a necessity for guidelines aimed at achieving a greater level of consensus among them. The most important of these guidelines include sincerity and turning to Allah - the Most High - and seeking His assistance and guidance from the outset. Furthermore, the competence of those undertaking this process is essential; they should possess a profound understanding of Islamic jurisprudence and its sciences, exhibit a fearless critical perspective, aspire to benefit from various Islamic jurisprudential schools of thought, and take into consideration the realities of the contemporary world, delving into them within specialized institutional frameworks that facilitate the exchange of knowledge and experiences.
أطروحة دكتوراه تخصص: الفقه وأصوله في كلية: العلوم الإسلامية
Keywords: الجدل _ الاجتهاد _ المقاصد _ النوازل.; Controversy _ Diligence _ Maquassid _ Updates